A new technique of closing a gastroatmospheric fistula with a rectus abdominis muscle flap. (27th March 2015) - Gupta, Rahul; Singh, Harjeet; Talukder, Shibojit; Verma, Ganga Ram
Abstract : Proximal enteroatmospheric fistulae are difficult to manage and carry high mortality from sepsis and electrolyte imbalances. Conservative management with total parenteral nutrition, exclusion of fistula, resection and anastomosis are conventional methods of treatment with low success rate. Providing muscle cover to manage an enteroatmospheric fistula is a noble concept. A postoperative high-output gastroatmospheric fistula (GAF) was repaired by superior epigastric artery-based rectus abdominis muscle flap (RAMF). Postoperative recovery was uneventful. This technique may be useful for closure of proximal enteroatmospheric fistulae that fail to heal through medical and conventional surgical management.